Routes of Transmission of Newly Emerging SARS-CoV-2: A Systematic Review (Bangladesh Journal of Infectious Diseases, 2020)
Background: In December 2019, a novel corona virus (SARS-CoV-2) causes atypical pneumonia now known as “corona virus disease 2019” (COVID-19) emerged in Wuhan, China and spread rapidly throughout the world.Objective: The purpose of the present study was to identify the different plausible routes of transmission of SARS-CoV-2 into the human body.Methodology: We searched electronic databases (MEDLINE, EMBASE, Science Citation Index and Chinese database) checked documents and references. We included all the studies regarding potential routes of transmission of SARS-CoV-2. All reviewers independently screened titles and abstracts, assessed studies for inclusion, appraised quality, and extracted data.Result: SARS-CoV-2 has been found to have higher level of transmissibility than other two pathogenic CoVs. Sustained human to human transmission of SARS-CoV-2 has already been established though the exact route of transmission is yet to be determined. Similar to other CoVs, respiratory droplet and contact with contaminated surfaces are considered as principle route of transmission of SARS-CoV-2 whereas aerosol, feco-oral, perinatal, ocular surface and transfusion transmissions are the plausible route of spreading of this highly pathogenic CoVs.Conclusion: In the current review, we summarize the potential route of transmission of SARS-CoV-2 in the light of previous SARS-CoV and MERS-CoV outbreaks to solidify the scientific basis on which important decisions can be made.Bangladesh Journal of Infectious Diseases, April 2020;7(suppl_1):S18-S31